Broader autistic phenotype in parents of children with autism: Autism Spectrum Quotient–Turkish version. Issue 1 (21st January 2013) - Kose, Sezen; Bora, Emre; Erermiş, Serpil; Özbaran, Burcu; Bildik, Tezan; Aydın, Cahide
<x xml:space="preserve">Abstract</x> Aims The Autism Spectrum Quotient (AQ) is a self‐assessment screening instrument for measuring the degree to which an individual of normal intelligence shows autistic traits. Genetic factors could be responsible for the relatives of individuals with autism exhibiting higher than normal rates of autism‐related impairments, referred to as the 'broader autism phenotype' (BAP). The aim of this study was to test whether there is a difference between the parents of autistic and those of typically developing children (TDC) on AQ scores in a Turkish sample. Method The AQ total and subscale scores of the 100 parents (47 fathers, 53 mothers) of children with autistic disorder (AD) were compared with the 100 parents (48 fathers, 52 mothers) of TDC. Results The parents of AD children scored significantly higher than the TDC parents on total AQ score, and two of five subscale scores; social skills, and communication. The other three subscales (attention to detail, attention switching, imagination) did not differentiate groups. There was no significant difference between mothers and fathers on any AQ scores, neither in the AD nor TDC group. The group × gender interaction was not significant on the total or the five subscale scores of AQ. Conclusion Social skill and communication subscales differentiate AD parents more successfully, and are more sensitive, as reported in other studies. The present findings confirm that social skill and communication impairments in parents of children with autism spectrum disorders are indicators of BAP.